The challenges of redistributing forest-related monetary benefits to local governments: a decade of logging area fees in Cameroon - Cerutti, P.O.; Lescuyer, G.; Assembe-Mvondo, Samuel; Tacconi, L. (2010)
The Cameroonian regulatory framework on forest, wildlife and fisheries requires logging companies to pay an Area Fee (AF), half of which must be redistributed to rural councils (40%) and villages (10%) neighbouring the logging concessions. The AF had the main objectives to provide a consistent contribution to the State budget and to improve rural livelihoods through an equitable and effective redistribution of forest-related benefits. After a decade of implementation, and about 85 million redistributed to about 50 councils, the literature unanimously evaluates the livelihood impacts of the distribution of the AF to communities as weak. Less comprehensive assessments have been carried out on the impacts of distribution of the AF to local governments. This paper discusses the potential of the AF as a tool for local development through local councils, with particular attention to the economic, equity and governance issues. One of the most significant findings is that mayors, although elected and unanimously blamed for embezzlements and mismanagement of the AF, are often only scapegoats in a complex political system that does not allow the rural population to directly sanction the misuse of the AF via the current electoral system.